Acoustic Analysis of the Baram Phonemes - Chalise, Krishna Prasad (Nepalese Linguistics, 2022)
Baram is a critically endangered Tibeto-Burman language spoken in the Gorkha District of central Nepal. This work carries out a preliminary acoustic study of the language. Baram plosives are acoustically characterized by VOT, the fricatives by the peak value and the affricates by the rise time and friction duration. Similarly, the nasals, lateral, trill and glides are characterized by formant structure. Similarly, the distribution of the F1 and F2 reveals the height of the tongue and frontness/backness of the vowels. The height of the vowels is also depicted by their intrinsic F0 as it increases as the height of the vowel increases. Baram has five diphthongs which are close diphthongs and the second target is always [i].